New paradigms of civil service: Kazakhstan and the United States, common issues and distinctive features - Begakhmetov, Aslan (Public Administration and Civil Service, 2013)
During reforms of civil service in the United States it was focused to make it more transparent and competitive comparing with the private sector. Vice-President Al Gore’s Commission proposed «to create a government that would work better and cost less.» Recent amendments to the Civil Service Law contain provision to create a new class of professional managers - «A» corps, responsible for the implementation of specific public policy tasks.